Jack Lenor Larsen: - Larsen, Jack Lenor (Harry N. Abrams, 1998)
Textile designer and weaver Jack Lenor Larsen reflects on his life and career in this illustrated memoir. From the post-war design scene to anecdotes about his collaborators I.M. Pei, Louis Kahn and Edward Larrabee Barnes, this is an account also covers Larsen's accomplishments as a gardener and garden designer, patron of younger artists and an avid collector of crafts from around the world